Fatigue life extension of welded steel structures by peening and TIG remelting - Alkarawi, Hassan (My University, 2019)
Fatigue is one of the most detrimental phenomena that endangers the life expectancy of welded steel structures. weld is susceptible to fatigue more than other parts because of the high stress concentration, the existing weld defects and the residual stress induced by welding. If the structure is in service, the structure might be already cracked. Different techniques were developed to extend the fatigue life of the structure and retrofit any existing crack, Peening and TIG remelting are just examples. A literature study is conducted to establish better understand on the effect of these two treatment methods their efficiency in crack retrofitting. The crack retrofitting experiments consist of two stages, pre-fatigue loading and loading after treatment. The first stage requires crack detection, different methods were investigated and the most efficient among them is the use of local strain drop measured by strain gauges. Peening treatment is found to be a function of the crack depth. Retrofitting the crack when it’s still shallow results in longer fatigue life. The treatment is found to be mainly relying on two effects: the crack orientation and the introduced residual stress. Peening causes a change in crack orientation which elongate the fatigue life. The higher and deeper compressive residual stress causes retardation of crack growth and deceleration of crack propagation. TIG remelting is another effecitve method which can retrofit crack deeper than peening. Its efficiency is a function of the crack depth and the fusion depth. Usually, the fusion depth is greater than 2mm which is greater than the peening indentation depth which hardly can reach 0.6 mm. In short, TIG is more appropriate to retrofit cracks deeper than 1mm while Peening results in longer life if the largest crack is shallower than 1mm.
Keywords: Fatigue; welding; Peening; HFMI; TIG remelting; TIG dressing; Life extension; Post weld treatment; Crack retrofiting; Crack detection; Linear elastic fracture mechanics; Strain gauge; fatigue crack; LEFM; Microhardness; Concentration factor; Gain factor